Cardiorespiratory and vascular function during stress - Ade, Carl Jacob (Kansas State University, 2013)
The primary aim of this dissertation was to evaluate the factors that contribute to the cardiorespiratory and vascular responses following exercise conditioning and microgravity deconditioning. The first study of this dissertation (Chapter 2) revealed that exercise training in the head down tilt posture, which places increases central blood volume compared to upright, results in cardiorespiratory adaptations in both upright and head down tilt postures which are not completely expressed with exercise training in the upright posture. These findings suggest that augmentation of the ventricular volume load during exercise training may result in adaptations that transfer across multiple body positions. In the second and third studies measurements of blood velocity and flow were performed via Doppler ultrasound. In Chapter 3 we observed that in the brachial and femoral arteries blood moves with a slightly blunted parabolic velocity profile that is very stable across a range of mean arterial pressures and downstream limb resistances. We concluded that these findings support the current calculations of shear rate based on the assumptions of laminar flow. With these assumptions confirmed, the investigation in Chapter 4 could be performed. We observed that acute exposure to a sustained antegrade shear rate, via unilateral forearm heating, increased measurements of flow-mediated dilation and the overall rate of adjustment for forearm blood flow and vascular conductance during dynamic handgrip exercise. These findings suggest that one potential stimulus for improvements in vascular function and health following exercise conditioning may be exposure to elevations in antegrade shear. Lastly in Chapter 5 we changed focus to the cardiorespiratory deconditioning following long-duration microgravity exposure. We retrospectively reviewed and analyzed previous investigations of microgravity deconditioning and demonstrated that the decrease in maximal O2 consumption ( O2max) occurs as a function of duration of exposure and that both convective and diffusive O2 transport pathways substantially contribute to this decline. In addition we reviewed the current literature and highlighted potential mechanisms, across several organ systems, which may contribute to this decline in O2max. Collectively, these studies revealed the breath of plasticity for cardiorespiratory adaptations to a variety of stressors.
Keywords: Cardiovascular exercise; Physiology (0719)